Low‐mid latitude D region ionospheric perturbations associated with 22 July 2009 total solar eclipse: Wave‐like signatures inferred from VLF observations. Issue 10 (9th October 2014) - Maurya, Ajeet K.; Phanikumar, D. V.; Singh, Rajesh; Kumar, Sushil; Veenadhari, B.; Kwak, Y.‐S.; Kumar, Abhikesh; Singh, Abhay K.; Niranjan Kumar, K.
Abstract We present first report on the periodic wave‐like signatures (WLS) in the D region ionosphere during 22 July 2009 total solar eclipse using JJI, Japan, very low frequency (VLF) navigational transmitter signal (22.2 kHz) observations at stations, Allahabad, Varanasi and Nainital in Indian Sector, Busan in Korea, and Suva in Fiji. The signal amplitude increased on 22 July by about 6 and 7 dB at Allahabad and Varanasi and decreased by about 2.7, 3.5, and 0.5 dB at Nainital, Busan, and Suva, respectively, as compared to 24 July 2009 (normal day). The increase/decrease in the amplitude can be understood in terms of modal interference at the sites of modes converted at the discontinuity created by the eclipse intercepting the different transmitter‐receiver great circle paths. The wavelet analysis shows the presence of WLS of period 16–40 min at stations under total eclipse and of period 30–80 min at stations under partial eclipse ( 85–54% totality) with delay times between 50 and 100 min at different stations. The intensity of WLS was maximum for paths in the partially eclipsed region and minimum in the fully eclipsed region. The features of WLS on eclipse day seem almost similar to WLS observed in the nighttime of normal days (e.g., 24 July 2009). The WLS could be generated by sudden cutoff of the photo‐ionization creating nighttime like conditions in the D region ionosphere and solar eclipse induced gravity waves coming to ionosphere from below and above. The present observations shed additional light on the current understanding of gravity waves induced D region ionospheric perturbations.